2020
DOI: 10.1159/000510712
|View full text |Cite
|
Sign up to set email alerts
|

Are Systemic Corticosteroids Causing Psoriasis Flare-Ups? Questionnaire for Danish Dermatologists, Gastroenterologists and Rheumatologists

Abstract: <b><i>Background:</i></b> Psoriasis flare-ups and the change of morphology from nonpustular to pustular psoriasis following tapering and withdrawal of systemic corticosteroids have been reported. Despite these risks, systemic corticosteroids are still widely prescribed for patients with psoriasis, but the knowledge about psoriasis flare-ups and whether the physicians take precautions during these treatments is limited. <b><i>Methods:</i></b> We conducted a questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Although the avoidance of systemic corticosteroids is typically recommended in the treatment of psoriasis vulgaris due to the possibility of rebound phenomenon, a recent meta-analysis questioned this commonly propagated belief and found low rates of rebound flares [ 83 ]. Generally, a gradual tapering of systemic corticosteroids was recommended for psoriatic patients [ 84 ]. In our study, systemic corticosteroids were administered in eight cases during the acute phase of psoriasis (including plaque, palmoplantar pustulosis, severe pustular, generalized pustular, and erythrodermic psoriasis and PsA) [ 11 , 38 , 44 , 52 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the avoidance of systemic corticosteroids is typically recommended in the treatment of psoriasis vulgaris due to the possibility of rebound phenomenon, a recent meta-analysis questioned this commonly propagated belief and found low rates of rebound flares [ 83 ]. Generally, a gradual tapering of systemic corticosteroids was recommended for psoriatic patients [ 84 ]. In our study, systemic corticosteroids were administered in eight cases during the acute phase of psoriasis (including plaque, palmoplantar pustulosis, severe pustular, generalized pustular, and erythrodermic psoriasis and PsA) [ 11 , 38 , 44 , 52 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ein erheblicher Teil dieser Patienten wurde mit systemischen Kortikosteroiden behandelt (8,7%). Eine Therapie mit systemischen Kortikosteroiden ist mit Risiken verbunden, kann sogar Schübe auslösen oder eine pustulöse Psoriasis verursachen, 34,35 und steht nicht im Einklang mit den Empfehlungen der nationalen und internationalen PSO‐Behandlungsleitlinien 14–18 . Die häufige Verwendung von Kortikosteroiden ist bereits aus früheren Veröffentlichungen bekannt, und unsere aktuellen Ergebnisse unterstreichen die Notwendigkeit, die Behandlungsalgorithmen in der Praxis zu verbessern 1,7,36,37 …”
Section: Diskussionunclassified
“…A survey of dermatologists and rheumatologists found that 47% had observed at least 1 psoriasis flare following treatment with oral steroids. 4 The reasons for the discrepancies include attribution bias and difficulty differentiating an expected recurrence of the dermatosis from a true rebound phenomenon. Finally, the risk of flares may differ depending on the underlying disease (eg, higher risk in patients with GPP).…”
Section: Psoriasis Flares and Rebound Phenomenon Following Exposure A...mentioning
confidence: 99%
“…We defined our inclusion criteria for suboptimal healing conditions as follows: patients aged [65 years with at least 1 comorbidity associated with poor wound healing (diabetes mellitus, cardiovascular disease, peripheral vascular disease, venous insufficiency, and smoking). 1,3,4 We routinely manage patients with wounds in the lower portion of the leg that heal by a secondary intention after Mohs micrographic surgery with petroleum jelly and a nonadherent dressing. Starting in January 2020, we began supplementing standard care with topical 0.5% timolol maleate ophthalmic solution (1 or 2 drops per day on wounds of #2 cm or [2 cm, respectively) for patients with suboptimal healing conditions.…”
Section: Topical Timolol Enhances Surgical Wound Healing In the Lower...mentioning
confidence: 99%